SUBSITUSI TEPUNG SEMOLINA DENGAN TEPUNG KULIT PISANG KEPOK (Musa balbisiania L.) DALAM PEMBUATAN SPAGETI HITAM - Sandi Hendra Yodi; Eddwina Aidila Fitria; Rera Aga Salihat; Inawaty Sidabalok; Leffy Hermalena; Wawan Sumarno (Fakultas Pertanian Universitas Riau, 2024)
This study aims to determine the effect of the substitution of semolina flour with kepok banana peel flour in making black spaghetti and to determine the best substitution treatment in making black spaghetti based on panellists assessment. A completely randomized design (CRD) including three replications and five treatment levels was employed in this investigation. ANOVA and DNMRT additional tests were used to examine the observation data at a 1% significance level. The observation data were analyzed using ANOVA and DNMRT further test at a significant level of 1%. The treatments in this study were the substitution of semolina flour with kepok banana peel flour (A=95% and 5%, B=90% and 10%, C=85% and 15%, D=80% and 20%, E=75% and 25%). The study's findings demonstrated that the water, ash, fat, protein, and carbohydrate content were significantly impacted by the substitution of semolina flour and banana peel flour. All treatments met the spaghetti quality requirements set by SNI 8777-2019, except for ash content and protein content in treatments D and E. The most preferred spaghetti was spaghetti with treatment C with a moisture content of 11.97%, ash content of 4.30%, fat content of 16.18%, protein content of 16.49%, and carbohydrate content of 79.54%. The results of this study are expected to contribute to the diversification of processed products based on semolina flour.